Are too-big-to-fail banks history in Europe? Evidence from overnight interbank loans - Eero Tölö; Esa Jokivuolle; Matti Virén (Bank of Finland, 2015)
We investigate how European banks' overnight borrowing costs depend on bank size. We use the Eurosystem's proprietary interbank daily loan data on euro-denominated transactions from 2008-2014. We find that large banks have had a clear borrowing cost advantage over small banks and that this premium increases progressively with the size of the bank. This result is robust with respect to subsamples, subperiods, time aggregation, and control variables such as Tier 1 capital ratio and rating. During episodes of financial stress, the size advantage becomes several times larger. However, we also find evidence that the new recovery and resolution framework for banks may have slightly reduced the borrowing cost advantage of larger banks in Europe.
URN:NBN:fi:bof-201512151482
Keywords: G21; G22; G24; G28; 330